Pengamanan Pemberian Kredit Bank Dengan Jaminan Hak Guna Bangunan - Bambang Catur PS (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2014)
Abstract: The Approval of Credit of Bank with the Guarantee of The Building Right. Bank has one of its functions as a credit provider that supports the sustainability of economy of the society. The loan given to the debitor will include the guarantee. One of the widely accepted guarantees is sertificate of the land, including sertificate of the Building Right. This study will explore to what extent this right is run and what are the obstacles and challenges of it will be discussed in this article. This article is based on doctrinal research in taking example the practice in BNI 46. Abstrak: Pengamanan Pemberian Kredit Bank Dengan Jaminan Hak Guna Bangunan. Bank memiliki salah satu fungsi sebagai penyedia kredit yang berguna bagi kelangsungan perekonomian masyarakat. Pinjaman yang diberikan kepada nasabah disertai dengan jaminan. Salah satu bentuk jaminan yang lazim diberikan adalah jaminan sertifikat hak atas tanah, yaitu Hak Guna Bangunan (HGB). Bagaimana praktek pengamanan ini dijalankan dan apa saja yang menjadi kendala dan tantangan akan dibahas dalam tulisan ini. Penelitian ini adalah penelitian normatif dengan mengambil contoh praktek di BNI 46. DOI: 10.15408/jch.v1i2.1468